DEVELOPMENT OF THE BASIS OF THE METHOD OF CONTROL OF THE EMERGENCY SITUATION RELATED TO FIRE AND EXPLOSION SAFETY OF LANDFILL: Array - Rashkevich, N.; Shershnyov, V.; Kondratiev, A.; Shevchenko О. (Municipal economy of cities. Series: «Economy science», 2021)
It is established that today there is no effective mathematical apparatus that adequately describes the process of preventing a dangerous event and preventing an emergency related to fire and explosion of solid waste disposal facilities close to settlements. The initial and boundary conditions of the existence of the mathematical apparatus are determined, which is the basis for the development of methods of counteracting the emergency. Humidity, the temperature of the landfill, the presence of oxygen at a certain point in time are factors that initiate the danger. The specific weight of the organic component, the value of the density of the array, the height of waste disposal affect the process of counteracting the danger.